Why the Reasons for the Collapse of the USSR Should Be Sought Before the Formation of the USSR. Article Two. The Strategic Error of Soviet Federalization as a Reflection on the Imperial Structure - V. A. Shamakhov; N. M. Mezhevich (Управленческое консультирование, 2021)
After the victory in the civil war, the question of the organization of power arose not only in the political, but also in the territorial-political sphere. For a long time, the Bolsheviks positioned the empire as a “prison of peoples”. After 1920 (Crimea), an adequate answer was needed from the authorities. The old party slogan influenced constitutional construction, and, to the Gorbachev era, the country came with the “sleeping norm” of the right to leave the Union Republic from the USSR.